Contribution of the green marketing mix to sustainable development Study of a sample of employees of EL-Zahra Hydro-oil Foundation in Wilayat of the El-Oued - Aouadi, Abdelkader; Mraoui, Rachida; Aouadi, Mostapha (Finance and Business Economies Review, 2019)
This study aims to show how the green marketing mix contributes In achieving sustainable development in economic institutions, It is one of the most important green economic topics this is due to the importance of the environment, It makes the institution green adapted to environmental variables and needs it is also earned by environmentally conscious consumers. This leads to the promotion of sustainable development, and in order to achieve this goal a study was conducted for a sample of the staff of the Zahra Hydrol Foundation in the Wilayat of the El-Oued. The results of this study were: The elements of the green marketing mix play a role in achieving sustainable development this is because of its relationship to the environmental dimension, The green marketing culture owned by consumers gives them sufficient environmental awareness and this is what makes the green company follow the green marketing strategy in order to preserve the environment.